EFFECTS OF YOHIMBINE AND ATIPAMEZOLE ON PLASMATIC GLUCOSE CONCENTRATION AND BLOOD GAS ANALYSIS IN DOGS INTOXICATED WITH TRIATOX® - ANDRADE, S. F.; SAKATE, M.; CROCCI, A. J. (Ars Veterinaria, 2008)
This study compared the effectiveness of either yohimbine or atipamezole in the reversion of hyperglycemia and blood gas alterations induced by Triatox®. Thirty dogs were equally divided into 3 groups (T, TY, and TA). Group T was given 2.5% Triatox® i.v. at 1 mg/kg; Group TY received the same dose of Triatox® followed by 0.1 mg/kg (2 mg/mL) yohimbine i.v. 30 minutes later; and Group TA received the same dose of Triatox® followed by 0.2 mg/kg (5 mg/mL)atipamezole i.v. 30 minutes later. Blood samples of every animal were drawn to measure plasma glucose concentration and blood gases at 0, 30, 60, 120 and 360 minutes after amitraz administration. Hyperglycemia was observed in group T (Triatox®); yohimbine (group TY) reverted the hyperglycemia induced by Triatox®, whereas atipamezole(group TA) was less effective than yohimbine to do so. There were no significant (p < 0.05) changes on blood gas analysis in all studied groups. Our results demonstrate the importance of more studies regarding the reversion of amitraz-induced hyperglycemia by the a2-adrenergic antagonists yohimbine and atipamezole. This procedure may be a crucial factor in the treatment of patients with alterations of the cardiorespiratory parameters and increased blood glucose levels owing to intoxication by this acaricide. KEY-WORDS: Amitraz. Yohimbine. Atipamezole. Glucose. Blood gas analysis. Triatox®.